Membangun Generasi Berkarakter melalui Manajemen Pendidikan Islam di Pesantren - Widodo, Wahyudi (Moderasi : Journal of Islamic Studies, 2024)
Character development is a cornerstone of education, crucial for preparing students to navigate contemporary challenges and future uncertainties. Pesantren, as traditional Islamic educational institutions, exemplify this effort by embedding religious and nationalistic values into the character-building process. This study investigates the management strategies of Islamic education at Pondok Pesantren Anwarul Huda, Malang, focusing on its contribution to student character formation. Using a qualitative research design, the study reveals the integral role of planning, organization, implementation, and evaluation in shaping student character. Planning involves engaging all stakeholders, including the community and guardians, while organization ensures the availability of resources and inclusive participation. Implementation integrates daily practices, core learning activities, and additional programs designed to foster exemplary behaviors. Evaluations, conducted at individual and collective levels, measure the effectiveness of these initiatives. Furthermore, the study explores the dual approach to character formation: a structured class-based model through Madrasah Diniyah sessions and a cultural framework rooted in pesantren traditions. Methods such as role modeling, advice, attention, and reward-punishment systems are applied to instill discipline and values. The findings emphasize the vital role of pesantren management in creating a conducive environment for holistic character development aligned with Islamic teachings.